Performance Of Composite Adsorbent In River Water Treatment - Teruna, Izzul Akmal (Universiti Sains Malaysia, 2017)
This study was carried out in order to access the potential of composite media by a combination of activated carbon, limestone, alginate as a binder with two different ratio, to remove organic and inorganic pollution that measured by concentration of turbidity, colour and Chemical Oxygen Demand (COD) in river water. In this present study, the batching experiment were conducted to decide the suitable factor for both ratio to effectively remove the involved parameter. Before the batching experiments, water characteristics were taken and COD were dismiss from batching experiment due to its low concentration. From the batch study, result and graph indicates that the suitable factor were 7g of dosage, 180 RPM of shaking speed, 75 minutes of contact and 90 minutes of settling time for ratio 7:3:2 (AC: LS: AG). Meanwhile for ratio 1:9:2 (AC: LS: AG), the suitable factor were 5g of dosage, 180 RPM of shaking speed, 95 minutes of contact time and 40 minutes of settling time. From the second batching experiments, for Ratio 7:3:2, the percentage removal of parameters were 92% for colour and 85% for turbidity. Meanwhile for Ratio 1:9:2, the percentage removal of parameters were 84% for colour and 60% for turbidity. This shows that 7:3:2 has been selected as the best ratio for composite adsorbent that consists of activated carbon, limestone and alginate. Meanwhile, the result from isotherms models for each of the parameters removal suggested that Freundlich isotherm was favourable with high coefficient of determination values for ratio 7:3:2 whereas the Langmuir isotherm were fit for adsorption process by ratio 7:3:2. For kinetic of adsorption, for each of the parameters removal by both ratios, pseudo-second-order model was suitable to describe kinetic of adsorption.